SAAED: Embedding and Deep Learning Enhance Accurate Prediction of Association Between circRNA and Disease - Liu, Qingyu; Yu, Junjie; Cai, Yanning; Zhang, Guishan; Dai, Xianhua (Frontiers in Genetics, 2022)
Emerging evidence indicates that circRNA can regulate various diseases. However, the mechanisms of circRNA in these diseases have not been fully understood. Therefore, detecting potential circRNA-disease associations has far-reaching significance for pathological development and treatment of these disease. In recent years, deep learning models are used in association analysis of circRNA-disease, but a lack of circRNA-disease association data limits further improvement. Therefore, there is an urgent need to mine more semantic information from data. In this paper, we propose a novel method called Semantic Association Analysis by Embedding and Deep learning (SAAED), which consists of two parts, a neural network embedding model called Entity Relation Network (ERN) and a Pseudo-Siamese network for analysis (PSN). ERN can fuse multiple sources of data and express the information with low-dimensional embedding vectors. PSN can extract the feature between CircRNA and disease for the association analysis. CircRNA-disease, CircRNA-miRNA, disease-gene, disease-miRNA， disease-lncRNA and disease-drug association information are used in this paper. More association data can be introduced for analysis without restriction. Based on CircR2Disease benchmark dataset for evaluation, five-fold cross-validation experiment showed an AUC of 98.92%, an accuracy of 95.39%, and a sensitivity of 93.06%. Compared with other state-of-the-art models, SAAED achieves the best overall performance. SAAED can expand the expression of the biological related information and is an efficient method for predicting potential circRNA-disease association.